DAMPAK KEBERADAAN TEMPAT PEMBUANGAN AKHIR (TPA) MUARA FAJAR TERHADAP SOSIAL EKONOMI MASYARAKAT DI KELURAHAN MUARA FAJAR KECAMATAN RUMBAI KOTA PEKANBARU - Maulida, Yusni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Research conducted to know The Impact Of Landfills Muara Fajar The Socio-Economic In The Village Of Muara Fajar Subdistrict Rumbai Pekanbaru City. Data used in this study is primary data and secondary data. Data analysis used with qualitative descriptive methods. The results of research in the know that the social impact existence of landfills Muara Fajar it is on in the health variable, environment and comfort. Where the health variable is diseases who often suffered by communities around the landfills Muara Fajar ie fever, diarrhea, skin disease and acute respiratory infections. The environmental variable the impact of landfills Muara Fajar inflict air pollution namely in the form of odor, of research obtainable people think sometimes smell that is there are 31 respondents or 45.59%. And the variable comfort overall that some communities assume disrupted as is the existence of landfills, of research obtainable 37 respondents or54.41%. While the economic impact the existence of landfills contained in the variable employment and income. Where the variable employment of existence landfills Muara Fajar about 28 respondents or 41.18%. And variable income produced by communities around the landfills Muara Fajar varies greatlyranging from the smallest Rp. 500.000,- to the largest Rp. 10.000.000,-.Keywords:Trash, Landfills, Impact and Socio-Economic